If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 6y = 0 Solving 14x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 14x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 14x + 0 = 0 + -6y 14x = 0 + -6y Remove the zero: 14x = -6y Divide each side by '14'. x = -0.4285714286y Simplifying x = -0.4285714286y
| 0.8x-0.9(18-4x)=-0.7(x-6) | | 64=2t^2-8 | | 8=6y-5y+4 | | 2x+9=7x+4x | | 7d+13=35-4b | | 21=y-(-6) | | 7x-x-1=11 | | -p+6p=6+2p | | -5(1-6r)=30-5r | | 0=t-12+3 | | 14-v=16 | | (7q+3)(4q+1)=0 | | 7x+6y=-14 | | 2m=3(m-10) | | 4(y-2)=29 | | 20-z=1 | | 7=7y+2 | | 9-4x=2+6 | | 5(x-2)+2(X+2)=10-2X | | r+3+12=-1 | | 20-2=1 | | 4x+1+2x+6x-10=180 | | 5n-4n+n-2=20 | | 14=0.1x+7 | | 4x-3(y-2)=15ty | | -4/1= | | 6w-1=8w+7 | | 7k=5 | | 17-y=0 | | x+.0507x=1012 | | -12s-30=-7s | | 4a+2p-2a+4p= |